Vahvan ruotsalaisen nuuskan vaikutus suun limakalvoon in vitro (The effect of Swedish snus with high nicotine content on oral mucosa in vitro) - Visuri, Julia (My University, 2022)
The use of snus has become more common in Finland in the 21st century. In Finland, Swedish moist snus is the predominant type of smokeless tobacco. The proportion of high-nicotine snus imported to Finland has increased. Swedish moist snus has many harmful health effects. In the oral cavity it causes, for example, localized lesions of the oral mucosa and gingival recession. The association between Swedish snus and oral cancer remains unclear. The research on Swedish snus and its health outcomes is limited. Especially, very little is known about the health outcomes of new type of snus with high nicotine content. The aim of this study was to investigate the effects of Swedish snus, and particularly snus with high nicotine content on oral mucosa in vitro. A three-dimensional cell culture method was used in this study. In this method, artificial oral mucosa is constructed using fibroblasts and keratinocyte cell line obtained from healthy human gingival biopsy samples. The artificial oral mucosa was then exposed to snus extract prepared by mixing Swedish snus with tissue culture medium. In this pilot in vitro study, Swedish snus caused impaired cell cohesion in the oral mucosa constructed in vitro. In addition, the artificial oral mucosa treated with strong snus containing 26 mg/g nicotine showed loss of epithelial cell polarity, cell atypia and some mitotic figures. The results of this preliminary study must be confirmed in future studies on Swedish snus and Swedish strong snus. Still, the findings give some reason to be concerned about the effect of strong snus on oral mucosa.

Nuuskan käyttö on yleistynyt Suomessa 2000-luvulla. Suomessa käytetään pääosin ruotsalaistyyppistä kosteaa nuuskaa. Korkean nikotiinipitoisuuden nuuskan osuus Suomeen tuotavasta nuuskasta on kasvanut. Ruotsalaisella nuuskalla on useita terveyshaittoja. Suussa se aiheuttaa esimerkiksi paikallisia limakalvovaurioita ja ienvetäymiä. Ruotsalaisen nuuskan ja suusyövän välinen yhteys on epäselvä. Ruotsalaisen nuuskan terveysvaikutuksia koskeva tutkimus on puutteellista. Erityisesti uusien korkean nikotiinipitoisuuden nuuskatuotteiden terveysvaikutuksista tiedetään hyvin vähän. Tämän tutkimuksen tavoitteena oli tutkia ruotsalaisen nuuskan vaikutusta in vitro -olosuhteissa luotuun suun limakalvoon. Erityisesti halusimme tutkia vahvan ruotsalaisen nuuskan vaikutuksia. Tutkimusmenetelmänä käytettiin kolmiulotteista raft-kudosviljelymallia. Tässä mallissa luotiin keinotekoista suun limakalvoa käyttämällä ihmisen suun limakalvoilta eristettyjä fibroblasteja ja keratinosyytti-solukantaa. Suun limakalvoa simuloiva kudosviljelmä altistettiin kudosviljelyelatusaineeseen sekoitetulle nuuskauutokselle. Tämän tutkimuksen tulosten mukaan ruotsalainen nuuska aiheutti keinotekoisessa suun limakalvossa epiteelin solujen koheesion hajoamista. Lisäksi vahvalle, 26 mg/g nikotiinia sisältävälle nuuskalle altistetussa keinolimakalvossa nähtiin epiteelin järjestäytymisen häiriötä, solujen atypiaa ja joitakin mitooseja. Tämän pilottitutkimuksen tulokset tulee kuitenkin varmistaa tulevissa ruotsalaista nuuskaa ja ruotsalaista vahvaa nuuskaa käsittelevissä tutkimuksissa. Löydökset herättävät kuitenkin huolta vahvan nuuskan vaikutuksista suun limakalvoon.
Keywords: kolmiulotteinen kudosviljelymalli, ruotsalainen kostea nuuska, nikotiini